Право як соціальне явище: особливості юридичного підходу - Петришин, О.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2007)
Автор раскрывает основания права как социального явления в особенностях юридического подхода. По его мнению, социологический подход з правопониманию та анализу процесса правового регулирования следует развивать и в части анализа вопросов государствоведения, которое при таких условиях становится правовое теорией организации и осуществления государственной власти в масштабах общества, то есть – правовой теории государства. An author exposes foundations of law as a social phenomenon under the legal approach. According to his
opinion, sociological approach towards the concept of law and analysis of the process of the legal regulation
should be developed in the part of the analysis of issues related to the study of state that under such conditions
becomes a legal theory of organization and realization of state power on the level ot society, that is a
legal theory of the state.